2003
DOI: 10.1109/ted.2002.808523
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nonlocal impact ionization on the speed of avalanche photodiodes

Abstract: Article:Hambleton, P.J., Ng, B.K., Plimmer, S.A. et al. (2 more ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…(5b) to find (5), shown at the bottom of the page. Here the are as defined earlier and given by (3).…”
Section: Mean Squared Current Responsementioning
confidence: 99%
See 1 more Smart Citation
“…(5b) to find (5), shown at the bottom of the page. Here the are as defined earlier and given by (3).…”
Section: Mean Squared Current Responsementioning
confidence: 99%
“…However, our modeling work [3]- [6], [11]- [13] predicts that those carriers which ionise at a distance shortly after the ballistic dead space, travel to this early ionization event at an average speed which is considerably higher than for carriers which ionise further downstream. We expect the effect to be important in thin APDs and that it more than compensates [5] for the slowing effect of dead space [1] which increases the number of carrier excursions back and forth across the multiplication region to maintain gain [7].…”
mentioning
confidence: 99%
“…Moreover, those carriers that impact ionize early on are found to possess speeds well above the saturated drift velocities [18]. In fact, Hambleton et al showed that this velocity-enhancement effect actually overcompensates for the dead-space effect [19]. In this paper, we show that the buildup time can be further reduced by considering a heterojunction multiplication region.…”
Section: Introductionmentioning
confidence: 63%
“…Despite its extreme simplicity this SMC model has proved capable of reproducing, at least qualitatively, many of the critical features of impact ionization and avalanche processes, including shapes of ionization path length pdf 34,36 , multiplication 34,36,37 , noise 34,36,37 , temporal behaviour 38,39 and temperature dependence of avalanche multiplication 40 .…”
Section: Monte Carlo Modelmentioning
confidence: 99%